THE IMPORTANCE OF DRAMA ACTIVITIES IN THE FOREIGN LANGUAGE CLASSROOM. - Ibragimova Dilafruz Shukhratovna; Mukhamadjonova Shukurona Madaminjon Qizi (TADQIQOTLAR.UZ, 2023)
Annotation: This article likely explores the significance of integrating drama activities into foreign language classrooms. It may discuss the impact of using drama in language learning, its benefits for students, and practical applications for educators.